2014
DOI: 10.1186/cc13821
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel competing risk models to evaluate the risk of nosocomial infection

Abstract: IntroductionRisk factor analyses for nosocomial infections (NIs) are complex. First, due to competing events for NI, the association between risk factors of NI as measured using hazard rates may not coincide with the association using cumulative probability (risk). Second, patients from the same intensive care unit (ICU) who share the same environmental exposure are likely to be more similar with regard to risk factors predisposing to a NI than patients from different ICUs. We aimed to develop an analytical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…5,12,44,78 If competing risks are present & absolute risks are of interest, apply competing risks models. 105,108,109,111,170 Multiple imputation of missing covariates must account for clustering & time-toevent, [136][137][138]140,143 using the event indicator and the Nelson-Aalen cumulative hazard.…”
Section: Recommendation Referencementioning
confidence: 99%
“…5,12,44,78 If competing risks are present & absolute risks are of interest, apply competing risks models. 105,108,109,111,170 Multiple imputation of missing covariates must account for clustering & time-toevent, [136][137][138]140,143 using the event indicator and the Nelson-Aalen cumulative hazard.…”
Section: Recommendation Referencementioning
confidence: 99%
“…In this case, a simpler risk metric analysis via logistic regression and risk odds ratios yielded similar results. 4 The phenomenon can be explained as follows: Even though patients with antibiotic treatment acquire less nosocomial bacteremia per ICU day at risk (nosocomial bacteremia HR, 0.83), their extended at-risk time in the ICU (discharge HR, 0.70) results eventually in an equal cumulative infection risk. Notably, the discharge hazard is much larger than the death hazard and is therefore the main determinant for the at-risk time.…”
Section: Accounting For Competing Events In Multivariate Analyses Of mentioning
confidence: 99%
“…For instance, in a multilevel competing risk analysis, 4 we showed that intensive care unit (ICU) patients who received antibiotic treatment 48 h before and/or after ICU admission had a lower hazard of acquiring a primary or secondary nosocomial bacteremia of any pathogen (hazard ratio [HR], 0.83; 95% CI, 0.77-0.88). For the competing events, antibiotic treatment is also associated with an increased death hazard (HR, 1.08; 95% CI, 1.04-1.13) and a reduced discharge hazard (HR, 0.70; 95% CI, 0.69-0.71), meaning that patients with antibiotic treatment remain at risk longer.…”
Section: Accounting For Competing Events In Multivariate Analyses Of mentioning
confidence: 99%
See 2 more Smart Citations